Evaluation of Autologous Blood in Pterygium Surgery With Conjunctival Autograft. Issue 2 (February 2019) - Zeng, Weijuan; Dai, Hanjun; Luo, Hong
Abstract : Purpose: Autologous blood has been used exploratively with conjunctival autograft in pterygium surgery. However, it is controversial whether autologous blood performed better than other fixation methods, including fibrin glue and sutures. This meta-analysis was conducted to evaluate the effectiveness of using autologous blood in pterygium surgery with conjunctival autograft. Methods: The study was conducted according to the PRISMA guidelines. The MEDLINE, Cochrane library, and Embase databases were systematically searched from their establishment until April 1, 2018. Randomized controlled trials comparing autologous blood with fibrin glue/suture in pterygium surgery with conjunctival autograft were included. The methodological quality of the included studies was assessed using the Cochrane risk of bias tool. Outcome measurements were recurrence, graft displacement, graft retraction, and surgical duration. Review Manager 5.3 (Cochrane Community, Cochrane Collaboration, London, UK) was used to perform the statistical analysis. When I 2 < 50%, statistical heterogeneity was considered acceptable, and a fixed-effects model was adopted; alternatively, the random-effects model was used. Results: Seven randomized controlled trials including 516 patients were finally included in the meta-analysis. Four studies with 379 patients compared autologous blood and fibrin glue. Autologous blood was inferior to fibrin glue with respect to surgical duration, graft retraction, and graft displacement. However, there was no statistical difference between the 2 groups in terms of the recurrence rate. Four studies with 152 patients compared autologous blood and traditional suturing. Autologous blood was superior to sutures in terms of surgical duration and inferior to sutures in terms of graft retraction. No difference was detected in terms of graft displacement and recurrence rate. Conclusions: In conclusion, autologous blood is an appropriate method for graft fixation in pterygium surgery. Current research suggests that autologous blood derivatives may be a promising approach after pterygium excision. However, this requires further confirmation.